Deontological aspects of sustainable consumption - Płachciak, Adam; Zaremba-Warnke, Sabina (Deontologiczne aspekty zrównoważonej konsumpcji, 2021)
The authors aimed to define the role of deontology in the implementation of sustainable development (SD) and show how consumers guided by the ethics of duty can become the initiator of common changes for SD. The article was prepared on the basis of qualitative research, and emphasizes that the concept of SD is strongly axiologically conditioned, and deontology plays a unique implementation role. The internalization of SD moral values is the key condition for the realization of sustainability both at macroeconomic and microeconomic level, i.e. enterprise management and consumer decisions. The authors indicate that in the market economy, in the era of globalization, the initiators of universal and evolutionary changes for SD may be consumers guided by the ethics of duty and supporting the sustainable consumerism movement. The article describes the main activities of the sustainable consumerism movement and the barriers slowing down its development
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2021; vol. 65, nr 2, s. 114-126